2006
DOI: 10.12944/cwe.6.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ground Water Quality and its Impact in and around Mangalam near Tirupathi, Andhra Pradesh, India

Abstract: Water is the most vital source and one of the precious natural resources of this planet. Due to industrialization and urbanization ground water quality is adversely affected. According to WHO, nearly 80% of all the diseases in human beings are caused by water. Many of the people of Mangalam, near Tirupathi, Andhra Pradesh, India are affected by pollution of drinking water. In the present study an attempt was made to assess the quality of ground water and its suitability for drinking purpose. EXPERIMENTAL Water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…According to WHO, nearly 80% of all the diseases in human beings are caused by water 11,12 . The water quality parameters of the various areas of Renigunta, near Tirupati indicates that the drinking water samples are contaminated and the quality is poor for drinking purpose.…”
Section: Resultsmentioning
confidence: 99%
“…According to WHO, nearly 80% of all the diseases in human beings are caused by water 11,12 . The water quality parameters of the various areas of Renigunta, near Tirupati indicates that the drinking water samples are contaminated and the quality is poor for drinking purpose.…”
Section: Resultsmentioning
confidence: 99%
“…Over exploitation of resources and improper waste disposal practices affected the drinking water quality. According to WHO, nearly 80% of all the diseases in human beings are caused by water 6,7 . Based on the results obtained for physicochemical analysis of ground water samples collected from different locations in the studied Chandragiri area, near Tirupati, it can be concluded that in some samples water quality parameters were beyond the permissible limit prescribed by WHO.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, membrane technology is considered to be a significant way to produce different grades of pure water, according to the feeding water. Treating water using membranes can be performed by using integrated membranes unit [9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…The deionized water can be easily produced using single-pass RO systems as the final process step with using high rejection (HR) membranes. RO is a cross-flow membrane separation process providing a level of filtration down to ionic levels for removal of dissolved salts [10][11][12][13][14][15][16][17][18] . According to the feeding water quality RO membranes can be formed in an array system to give an overall concentrate stream flow as low as 10% of the feeding supply, equating to an overall system recovery of up to 90%.…”
Section: Introductionmentioning
confidence: 99%